3D‐Printed Silicone Substrates as Highly Deformable Electrodes for Stretchable Li‐Ion Batteries. Issue 3 (21st November 2022) - Praveen, Sekar; Kim, Taehyung; Jung, Soon Phil; Lee, Chang Woo
Abstract: Stretchable energy storage devices receive a considerable attention at present due to their growing demand for powering wearable electronics. A vital component in stretchable energy storage devices is its electrode which should endure a large and repeated number of mechanical deformations during its prolonged use. It is crucial to develop a technology to fabricate highly deformable electrode in an easy and an economic manner. Here, the fabrication of stretchable electrode substrates using 3D‐printing technology is reported. The ink for fabricating it contains a mixture of sacrificial sugar particles and polydimethylsiloxane resin which solidifies upon thermal curing. The printed stretchable substrate attains a porous structure after leaching the sugar particles in water. The resulting printed porous stretchable substrates are then utilized as electrodes for Li‐ion batteries (LIBs) after loading them with electrode materials. The batteries with stretchable electrodes exhibit a decent electrochemical performance comparable to that of the conventional electrodes. The stretchable electrodes also exhibit a stable electrochemical performance under various mechanical deformations and even after several hundreds of stretch/release cycles. This work provides a feasible route for constructing LIBs with high stretchability and enhanced electrochemical performance thereby providing a platform for realizing stretchable batteries for next generation wearable electronics. Abstract : The fabrication of stretchable electrode substrates by using 3D‐printing technology is reported. The ink for fabricating stretchable electrode contains a mixture of sugar powders and polydimethylsiloxane resin. The fabricated batteries with stretchable electrodes exhibit a decent electrochemical performance. This feasible battery fabrication route proves a platform for realizing stretchable batteries for next generation wearable electronics.